The Effectiveness of Play Therapy to Minimize Hyperactive Behavior of Mild Intellectual Disabilities Student in 1st Grade at SLB C Setya Darma Surakarta Academic Year of 2018/2019 - Afifah, Fauzia Nur; Anwar, Mohammad; Hermawan (Indonesian Journal of Disability Studies, 2019)
This research aims to examine the effectiveness of play therapy to minimizing hyperactive behavior of mild intellectual disabilities student in 1st grade at SLB C Setya Darma Surakarta academic year of 2018/2019. The method for this research is using single subject research with particular intervention. The research was using A-B-A design, with first baseline as the original, then intervene the subject, and finally implemented the result to the second baseline afterward. Research subject in this study was a mild intellectual disabilities student who have hyperactive behavior in 1st grade at SLB C Setya Darma Surakarta academic year of 2018/2019. Data collection technique in this research was using observation and interview. This research was analysed with descriptive statistics and visual graph analysis technique. The result showed that there was a reduction to hyperactive behaviour. The average frequency in student's hyperactive behaviour at the first time was 34 times with duration of 20 minutes in 30 minutes lesson. Thereafter, the reduction was showed in the intervene stage to 28.5 with duration of 15 minutes in 30 minutes lesson. Whereas in the second baseline, the average frequency was 18.75 with duration of 10 minutes in 30 minutes lesson. Based on research result, it can be concluded that play therapy is effective in minimizing the behavior of mild intellectual disabilities student in 1st grade at SLB C Setya Darma Surakarta Academic Year of 2018/2019.